Innovation of Electronic Land Rights Certificate Service at the Surabaya City Land Agency II - Afrizal Pratama; Nihayatus Sholihah; Zainal Fatah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This abstract summarizes the innovation in land administration services through the implementation of Electronic Land Rights Certificates (e-Certificates) by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). The policy responds to persistent challenges in conventional land certificate services, including lengthy bureaucratic procedures, limited transparency, and risks of document duplication and forgery. The study focuses on the implementation of e-Certificate services at the Surabaya City Land Office II, aiming to analyze the effectiveness of the innovation, supporting and inhibiting factors, and its impact on public service quality. A descriptive qualitative approach is employed, utilizing Rogers’ Diffusion of Innovation theory (1971) with five key indicators: relative advantage, compatibility, complexity, trialability, and observability. Data collection methods include document analysis, in-depth interviews, and field observation. Findings indicate that the e-Certificate provides significant benefits, such as time efficiency, enhanced data security, and improved transparency. The innovation also aligns with national priorities for digital transformation and bureaucratic reform. However, notable complexity persists due to limited digital literacy among the public and adaptation challenges faced by employees. Limited-scope pilot implementation supports iterative system improvements, while observable outcomes include accelerated services and increased public trust. Key enabling factors consist of strong national policy support, advanced digital infrastructure in Surabaya, and organizational commitment. Conversely, constraints include limited human resources, resistance to organizational change, and data security concerns. Overall, the e-Certificate innovation at the Surabaya City Land Office II has generated new public value through faster, more efficient, and accountable services, establishing a model for advancing digital transformation in land administration across Indonesia.